Peningkatan Keterampilan Menulis PuisiMelalui Model Picture and Picture Dengan Menggunakan Media GambarPada Kelas V MI Darul Iman - Aniati Anas; Amrul Amrul; Hestie Ariestina; MS Viktor Purhanudin; Jepri Utomo; Aryo De Wibowo Muhammad Sidik (Departement of Mathematics Education, 2023)
A study has been carried out entitled Improving Poetry Writing Skills Through Picture and Picture Models with Image Media in Class V MI Darul Iman Students. In learning to write poetry using the technique of using picture and picture models with image media. A learning method that invites students to observe a set of pictures in class. The picture-and-picture method is also very useful in learning poetry. The essence of writing poetry is the result of recording events or pictures of interesting objects that are poured through his mind into written language. The picture and picture method here can inspire students to express themselves in poetry, by observing an interesting picture. The research was conducted at MI Darul Iman in class V and this research was carried out in 2 cycles and 4 stages in each cycle namely Planning, Action, Observation, and Reflection. Based on the results of research that has been carried out using the picture and picture model with image media can improve teachers in learning poetry writing skills in class V MI Darul Iman students, it can also increase student activity in learning poetry writing skills and can increase the class average value in the cycle 1 with a score of 66.67 with a completeness percentage of 33.33% increased in cycle 2 to 80.07 with a completeness percentage of 86.66%. There was an increase in student scores of 53.33% from cycle 1 to cycle 2 with Very Good criteria.